Efektivitas Anti Jamur Sistemik Terhadap Dermatofitosis - Warouw, Mathilda W.; Kairupan, Tara S.; Suling, Pieter L. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: Dermatophytosis or tinea is the most frequent fungal infection in the world caused by the dermatophyte fungi group. These dermatophytes infect the stratum corneum of the skin, hair shaft, and nails. Systemic antifungals are one of the treatment options for dermatophytosis, especially in cases of widespread infection or failure of topical therapy. This study aims to determine the effectiveness of various systemic antifungals (griseofulvin, terbinafine, and azole derivatives) against dermatophytosis. This study was in the form of a literature review by searching and collecting data using the PubMed and ClinicalKey databases, with the keywords antifungal sistemik, dermatofitosis, tinea (bahasa Indonesia), and systemic antifungal, dermatophytosis, tinea (English). Based on the results of the literature search, 10 articles were found that match the inclusion and exclusion criteria. From the article review, it is known that the effectiveness of systemic antifungal therapy against dermatophytosis varies according to the classification and duration of therapy. In conclusion, systemic antifungals in the treatment of dermatophytosis have been shown to be effective.Keywords: systemic antifungal, dermatophytosis, tineaÂ Â Abstrak: Dermatofitosis atau kata lainnya tinea merupakan infeksi jamur paling sering di dunia yang disebabkan oleh golongan jamur dermatofita. DermatofitaÂ ini menginfeksi stratum korneum kulit, batang rambut, dan kuku. Antijamur sistemik merupakan salah satu pilihan terapi dermatofitosis terutama pada kasus infeksi luas atau kegagalan terapi topikal. Penelitian ini bertujuan untuk mengetahui efektivitas dari berbagai antijamur sistemik (griseofulvin, terbinafin, dan turunan azole) terhadap dermatofitosis. Penelitian ini berbentuk literature review dengan pencarian dan pengumpulan data menggunakan database PubMed dan ClinicalKey, dengan kata kunci antijamur sistemik, dermatofitosis, tinea (Bahasa Indonesia), serta systemic antifungal, dermatophytosis, tinea (Bahasa Inggris). Berdasarkan hasil pencarian literatur didapatkan 10 artikel yang sesuai dengan kriteria inklusi dan eksklusi. Dari tinjauan artikel diketahui efektivitas dari pemberian terapi antijamur sistemik terhadap dermatofitosis bervariasi sesuai klasifikasi dan durasi terapi. Sebagai simpulan, antijamur sistemik pada terapi dermatofitosis terbukti efektif.Kata kunci: antijamur sistemik, dermatofitosis, tinea.